An engine, not a camera : how financial models shape markets - MacKenzie, Donald A. (Inside technology., 2006)
This pioneering work in the social studies of finance describes how the emergence of modern finance theory has affected financial markets in fundamental ways. Paraphrasing Milton Friedman, the author says that economic models are an engine of inquiry rather than a camera to reproduce empirical facts.